Axillary Staging of Early‐Stage Invasive Breast Cancer by Ultrasound‐Guided Fine‐Needle Aspiration Cytology: Which Ultrasound Criteria for Classifying Abnormal Lymph Nodes Should Be Adopted in the Post‐ACOSOG Z0011 Trial Era?. (23rd March 2016) - Zhu, Ying; Zhou, Wei; Zhou, Jian-qiao; Fei, Xiao-chun; Ye, Ting-Jun; Huang, Ou; Chen, Xiao-song; Zhan, Wei-Wei
Abstract : Objectives: Ultrasound (US)‐guided fine‐needle aspiration cytology (FNAC) is able to identify patients with extensive node involvement before surgery. In this study, we aimed to establish the optimal US criterion to identify abnormal lymph nodes on US‐guided FNAC for detection of patients with 3 or more metastatic axillary nodes. Methods: A total of 445 axillae from 443 patients with histologically confirmed invasive breast cancer (cT1–2 cN0) were examined with US at Ruijin Hospital from August 2013 to August 2014. Ultrasound‐guided FNAC was performed on suspicious nodes when the cortex was eccentrically or concentrically thickened to greater than 2 mm; 269 axillae (60.4%) met the criterion and underwent US‐guided FNAC. We retrospectively analyzed the US characteristics of axillary lymph nodes, the US‐guided FNAC results, and the extent of axillary nodal involvement. For diagnostic performance, the sensitivity, specificity, and receiver operating characteristic curves were obtained. Results: Eighty‐six patients (19.4%) were confirmed to have 3 or more positive lymph nodes by pathologic analysis. There was a significant association between the morphologic change in the most suspicious node and the extent of axillary nodal involvement ( P < .001). When we applied the cutoff point (cortical thickness >3.5 mm) at which the maximal sum of sensitivity and specificity for diagnosis of 3 or more axillary lymph node metastases was achieved, we found that the sensitivity and specificity were 75.6% and 82.7%, respectively. When combining this criterion with US‐guided FNAC of the most suspicious nodes, the sensitivity and specificity were 64.2% and 94.5%, and 36.1% of cases could be spared an unnecessary 1‐step axillary lymph node dissection. Conclusions: Cortical thickness of greater than 3.5 mm in the most suspicious nodes is appropriately predictive of patients with 3 or more tumor‐involved axillary nodes. When this criterion for US‐guided FNAC was adopted, a group of patients with 1 or 2 metastatic nodes could be spared unnecessary 1‐step axillary lymph node dissection.